Perceived Organisational Support’s relationship with Psychological Empowerment: A Review of Literature - Luxmi,; Sneha, (Gyan Management Journal, 2023)
Current research examined the role of psychological empowerment of  employees with the perceived organisational supports of employees.  There are a very few researches were conducted to explore the relationship  between the two variables perceived organisational support and  psychological empowerment. Here the current research is based on review  of previous researches to explore the kind of relationship exist between  perceived organisational support and psychological empowerment.  The results of the study reveals that an organisation’s strength is depend  upon the attitude of their employees toward them. If the organisation’s  employees feel that their organisation doesn’t worth their effort, so they  start loosing interest in the Organisations work. Various researchers have  supported the fact that the employees who are more committed to the  organisation are high in performance, reduce absenteeism and try to stay  in their current organisation for longer duration.
Keywords: Psychological Empowerment; organisational support